Comparison of measured and modelled spectral UV irradiance at Izaña high mountain station: estimation of the underlying effective albedo. (27th April 2015) - García, R. D.; Cachorro, V. E.; Cuevas, E.; Toledano, C.; Redondas, A.; Blumthaler, M.; Benounna, Y.
ABSTRACT: In this work, we have carried out a comparison study between measured and modelled direct and global ultraviolet (UV) (300–400 nm) spectral irradiances and the determination of the surface effective albedo at the high altitude Izaña Observatory [IZO; 2400 m above sea level (a.s.l.)] located in Tenerife (Canary Islands, Spain). The spectral measurements were performed with a Bentham spectroradiometer during the Quality Assurance of Solar Ultraviolet Spectral Irradiance Measurements (QASUME) comparison campaign in June 2005. The simulations were obtained with the LibRadtran radiative transfer model. The model input parameters, such as total ozone and aerosol optical depth (AOD), were measured at IZO. The comparison between measured and modelled direct solar radiation component was made at 0.5 nm spectral resolution, showing excellent agreement, with differences below 5% for solar zenith angle (SZA) < 60°. These differences were attributed to the effect of the underlying surface albedo due to the frequent existence of a sea of clouds below the station altitude. The underlying surface albedo was determined using different methods. In spite of the variability of this parameter through the day due to the strong influence and variable structure of these underlying clouds, the mean of this effective surface albedo in the UV region gives a value between 0.2 and 0.5 in the UV range, 10 times higher than the local surface albedo (0.02–0.05).